Optimalisasi Kepemimpinan Pendidikan dan Penguatan Permodalan dalam Meningkatkan Kinerja Koperasi Sekolah - Dwi Retnani; Elsa Ngatiatun Nazillah; Hawa Rokhmatiah; Siswadi Siswadi (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2026)
This study aims to analyze strategies for optimizing the capital structure of school cooperatives to improve performance and ensure business sustainability. The study is motivated by the limited capital capacity of school cooperatives, which is influenced by low member participation, weak managerial practices, and dependence on external funding sources. This research employs a qualitative approach using a library research design by reviewing relevant scientific sources such as journal articles, books, and academic publications. Data analysis was conducted descriptively by identifying, categorizing, and synthesizing findings from previous studies. The results indicate that the capital of school cooperatives is derived from internal sources and external loans, yet its growth remains limited. The main challenges include low member participation, limited managerial capacity, and suboptimal use of technology in cooperative management. Therefore, capital optimization strategies should focus on enhancing member participation, strengthening management capacity, diversifying business units, and expanding partnerships alongside digital transformation. This study contributes theoretically to the development of cooperative management studies and practically provides insights for school cooperative managers in designing more effective and sustainable strategies